Effect of quantitative intraocular pressure reduction on visual field defect progression in normal tension glaucoma under medical therapy applying Markov model - Yoshikawa K (Dove Medical Press, 2018)
Keiji Yoshikawa,1 Kazunori Santo,2 Hiroko Hizaki,2 Masayo Hashimoto2 1Yoshikawa Eye Clinic, Machida, Tokyo, Japan; 2Japan Medical Affairs, Santen Pharmaceutical Co., Ltd, Osaka, Japan Purpose: To quantitatively evaluate the association of intraocular pressure (IOP) reduction with visual field defect (VFD) progression in normal tension glaucoma (NTG) under medical therapy. Patients and methods: Clinical data for 622 eyes of 311 primary open-angle glaucoma and NTG patients were collected from April 2006 to March 2016. Of these patients, those with normal IOP, glaucomatous VFD by Anderson’s criteria, corrected visual acuity ≥0.7, >5 years of medical therapy, ≥5 visual field tests at least five times at 12-month intervals, visual field testing reliability coefficients of ≤33%, and mean deviation (MD) exceeding below -20 dB in the initial visual field test were included in this retrospective data analysis. MD and IOP data were collected at baseline and after 5 years. Following MD categorization into stages I to IV, stage transition matrices were generated using a Markov model to evaluate VFD changes. Eyes were divided based on IOP reduction (0%, 10%, 15%, 20%, 25%, 30%) from baseline. VFD aggravations were compared using the Markov model and MD slopes with IOP reduction rates as cutoff values. Results: Overall, 132 eyes of 132 NTG patients fulfilled the eligibility criteria. MD decreased significantly (P<0.0001) at 5 years vs baseline. During follow-up, visual field stage using the Markov model was constant in ~60%, with transitions in ~40%. IOP decreased significantly (P<0.001) at 5 years vs baseline. Though MD slopes did not differ significantly between each of the groups that achieved the various IOP reduction cut-off values and the corresponding group that did not achieve the cut-off values, a significant difference (P=0.0432) in VFD was found between the group that achieved the 25% cut-off value and the group that did not when evaluated using the Markov model. Conclusion: In NTG patients, VFD aggravation was significantly suppressed in groups with IOP reductions of ≥25% from baseline. Keywords: normal tension glaucoma, visual field defect (VFD) progression, long-term follow-up, intraocular pressure reduction, Markov model